Facilitating Learner-Centered Transition to Residency: A Scoping Review of Programs Aimed at Intrinsic Competencies. Issue 1 (17th September 2020) - Kassam, Aliya; Nickell, Leslie; Pethrick, Helen; Mountjoy, Margo; Topps, Maureen; Lorenzetti, Diane L.
Abstract: Phenomenon: There is currently a move to provide residency programs with accurate competency-based assessments of their candidates, yet there is a gap in knowledge regarding the role and effectiveness of interventions in easing the transition to residency. The impact of key stakeholder engagement, learner-centeredness, intrinsic competencies, and assessment on the efficacy of this process has not been examined. The objective of this scoping review was to explore the nature of the existing scholarship on programs that aim to facilitate the transition from medical school to residency. Approach: We searched MEDLINE and EMBASE from inception to April 2020. Programs were included if they were aimed at medical students completing undergraduate medical training or first year residents and an evaluative component. Two authors independently screened all abstracts and full text articles in duplicate. Data were extracted and categorized by type of program, study design, learner-centeredness, key stakeholder engagement, the extent of information sharing about the learner to facilitate the transition to residency, and specific program elements including participants, and program outcomes. We also extracted data on intrinsic (non- Medical Expert ) competencies, as defined by the CanMEDS competency framework. Findings: Of the 1, 006 studies identified, 55 met the criteria for inclusion in this review. The majority of the articles that were eligible for inclusion were from the United States (n = 31, 57%). Most of the studies (n = 47, 85%) employed quantitative, or mixed method research designs. Positive outcomes that were commonly reported included increased self-confidence, competence in being prepared for residency, and satisfaction with the transition program. While a variety of learner-centered programs that focus on specific intrinsic competencies have been implemented, many (n = 29, 52%) did not report engaging learners as key stakeholders in program development. Insights: While programs that aim to ease the transition from medical school to residency can enhance both Medical Expert and other intrinsic competencies, there is much room for novel transition programs to define their goals more broadly and to incorporate multiple areas of professional development. The existing literature highlights various gaps in approaches to easing the transition from medical school to residency, particularly with respect to key stakeholder engagement, addressing intrinsic CanMEDS competencies, and focusing on individual learners' needs.